The Recommendations of the Russian Gastroenterological Association on the Diagnostics and the Treatment of Chronic Pancreatitis (Draft) - V. T. Ivashkin; I. V. Mayev; O. S. Shifrin; A. A. Sheptulin; A. V. Okhlobystin; Yu. A. Kucheryavyy (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.